Association of Poor Sleep With Depressive and Anxiety Symptoms by HIV Disease Status: Women's Interagency HIV Study. (1st February 2022) - Daubert, Elizabeth; French, Audrey L.; Burgess, Helen J.; Sharma, Anjali; Gustafson, Deborah; Cribbs, Sushma K.; Weiss, Deborah Jones; Ramirez, Catalina; Konkle-Parker, Deborah; Kassaye, Seble; Weber, Kathleen M.
Abstract : Background: Sleep disturbances are prevalent in women living with HIV (WLWH) and can affect mental health and overall quality of life. We examined the prevalence and predictors of poor sleep quality in a US cohort of WLWH and HIV-uninfected controls and the relationship between sleep quality and mental health symptom burden stratified by HIV disease status (viremic WLWH, aviremic WLWH, and HIV-uninfected women). Methods: Sleep quality was assessed using the Pittsburgh Sleep Quality Index in 1583 (400 viremic WLWH, 723 aviremic WLWH, and 460 HIV-uninfected women) Women's Interagency HIV Study participants. Depressive and anxiety symptoms were concurrently assessed using the Center for Epidemiological Studies-Depression (CES-D) scale and General Anxiety Disorder (GAD-7) scale. Associations between poor sleep quality (global Pittsburgh Sleep Quality Index >5) and both high depressive (CES-D ≥16) and anxiety (GAD-7 ≥10) symptoms were each assessed by HIV disease status using multivariable logistic regression models. Results: Prevalence of poor sleep quality in the overall sample was 52%, differed by HIV disease status ( P = 0.045), and was significantly associated with high depressive and anxiety symptoms in (1) viremic WLWH, (2) aviremic WLWH, and (3) HIV-uninfected women [CES-D: (1) adjusted odds ratio (aOR) = 7.50, 95% confidence interval (CI): 4.10 to 13.7; (2) aOR = 4.54, 95% CI: 3.07 to 6.73; and (3) aOR = 6.03, 95% CI: 3.50 to 10.4; GAD-7: (1) aOR = 5.20; 95% CI: 2.60 to 10.4, (2) aOR = 6.03; 95% CI: 3.67 to 9.91, and (3) aOR = 6.24; 95% CI: 3.11 to 12.6]. Conclusions: Poor sleep quality is highly prevalent, as is mental health symptom burden, among WLWH and HIV-uninfected controls. Future longitudinal studies are necessary to clarify the directionality of the relationship.